Supplementary food for Neoseiulus californicus boosts biological control of Tetranychus urticae on strawberry. Issue 7 (4th February 2019) - Vacacela Ajila, Henry E; Colares, Felipe; Lemos, Felipe; Marques, Pedro H; Franklin, Eliza C; Santos do Vale, Willian; Oliveira, Eugênio E; Venzon, Madelaine; Pallini, Angelo
Abstract: BACKGROUND: A wide range of supplementary food resources can be offered to generalist predatory mites to improve their survival and reproduction and enhance their persistence in the environment. We investigated the relative suitability of different pollen types for the survival and reproduction of Neoseiulus californicus and its life history on a mixed diet of pollen and prey. We also evaluated the population dynamics of Tetranychus urticae in the presence of N. californicus with or without pollen, and in comparison to Phytoseiulus macropilis . RESULTS: Survival and reproduction of N. californicus adults were satisfactory on exclusive diets of T. urticae, cattail pollen, palm pollen and bee pollen. However, mites did not reproduce when fed only pollen during both immature and adult stages. Both predatory mites successfully controlled T. urticae . Although the specialist P. macropilis was more efficient in suppressing the pest population in the short term, it abandoned plants at low prey densities, whereas N. californicus performed better and persisted longer under prey scarcity. CONCLUSION: N. californicus is an efficient biological control agent of T. urticae and the provision of supplementary food could retain them in the crop prior to the arrival of the pest or in periods of prey scarcity. © 2019 Society of Chemical Industry Abstract : The aggressiveness of pests forces the improvement of existing alternative controls. This study shows how the efficiency of biological control agents can be improved through supplementary food provision.